Trimethylamine N-Oxide Reduces the Susceptibility of Escherichia coli to Multiple Antibiotics - Qiao, Jiaxin; Liang, Yan; Wang, Yao; Morigen, (Frontiers in Microbiology, 2022)
Trimethylamine N-oxide (TMAO), an important intestinal flora-derived metabolite, plays a role in the development of cardiovascular disease and tumor immunity. Here, we determined the minimum inhibitory concentration (MIC) of antibiotics against Escherichia coli under gradient concentrations of TMAO and performed bacterial killing analysis. Overall, TMAO (in the range of 10~100 mM) increased the MIC of quinolones, aminoglycosides, and β-lactams in a concentration-dependent manner, and increased the lethal dose of antibiotics against E. coli. It implies that TMAO is a potential risk for failure of anti-infective therapy, and presents a case for the relationship between intestinal flora-derived metabolites and antibiotic resistance. Further data demonstrated that the inhibition of antibiotic efficacy by TMAO is independent of the downstream metabolic processes of TMAO and the typical bacterial resistance mechanisms (mar motif and efflux pump). Interestingly, TMAO protects E. coli from high protein denaturant (urea) stress and improves the viability of bacteria following treatment with two disinfectants (ethanol and hydrogen peroxide) that mediate protein denaturation by chemical action or oxidation. Since antibiotics can induce protein inactivation directly or indirectly, our work suggests that disruption of protein homeostasis may be a common pathway for different stress-mediated bacterial growth inhibition/cell death. In addition, we further discuss this possibility, which provides a different perspective to address the global public health problem of antibiotic resistance.